PENGARUH STRATEGI INOVASI TERHADAP KINERJA BISNIS PERUSAHAAN PENGADAAN JASA CLEANING SERVICE - Carissa Alodia Pratama; Abdulah Rakhman (Sekolah Tinggi Pariwisata Mataram, 2022)
In this era of globalization, of course, brings many changes and transformation to various companies and the business environment, where they competes with each other which results in increasing competition. Therefore, companies or business actors who see the current situation finally realize that they must try to provide the best service for consumers in order to compete with other competitors in the field. The research method used is judgement sampling by collecting data through a questionnaire distributed to 100 respondents who are currently working as employees at PT Cahaya Pratama Megah with positions as area leader, area supervisor and also an employee at the head office. The measuring instrument in this research is validity test, reliability test, percentage, average, likert scale, classical assumption test, and multiple linear regression test. The tool used is SPSS 25.0. This study concludes that the market leadership orientation variable has no effect on business performance. While the variables of the type of innovation and innovation sources have a positive and significant effect on business performance.